Fabrication of nanocomposites through diffusion bonding under high-pressure torsion - Kawasaki, Megumi; Han, Jae-Kyung; Lee, Dong-Hyun; Jang, Jae-il; Langdon, Terence G. (Journal of materials research, 2018)
This report summarizes a recent study demonstrating simple and rapid synthesis of a new Al–Mg alloy system and ultimately synthesizing a metal matrix nanocomposite, which was achieved by processing stacked disks of the two dissimilar metals by conventional high-pressure torsion (HPT) processing. The synthesized Al–Mg alloy system exhibits exceptionally high hardness through rapid diffusion bonding and simultaneous nucleation of intermetallic phases with increased numbers of HPT turns through 20, and improved plasticity was demonstrated by increasing strain rate sensitivity in the alloy system after post-deformation annealing. An additional experiment demonstrated that the alternate stacking of high numbers of dissimilar metal disks may produce a faster metal mixture during HPT. Metal combinations of Al–Cu, Al–Fe, and Al–Ti were processed by the same HPT procedure from separate pure metals to examine the feasibility of the processing technique. The microstructural analysis confirmed the capability of HPT for the formation of heterostructures across the disk diameters in these processed alloy systems. The HPT processing demonstrates a considerable potential for the joining and bonding of dissimilar metals at room temperature and the expeditious fabrication of a wide range of new metal systems.